2016
DOI: 10.1038/nrurol.2016.157
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in male reproduction: effect of paternal diet on sperm quality and offspring health

Abstract: Epigenetic inheritance and its underlying molecular mechanisms are among the most intriguing areas of current biological and medical research. To date, studies have shown that both female and male germline development follow distinct paths of epigenetic events and both oocyte and sperm possess their own unique epigenomes. Fertilizing male and female germ cells deliver not only their haploid genomes but also their epigenomes, which contain the code for preimplantation and postimplantation reprogramming and embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
150
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(156 citation statements)
references
References 179 publications
0
150
2
4
Order By: Relevance
“…For instance, epidemiologic evidences showed that environmental challenges imposed on the father, such as stress, specific diets, toxins, tobacco smoking and alcohol consumption, have been found to influence the development of the offspring via the non-genetic alterations within sperm including small non-coding RNAs, DNA damage, DNA methylation and histone modifications (Chen et al 2016b, Rando 2016, Schagdarsurengin & Steger 2016, Fullston et al 2017.…”
Section: Obesity Influences Sperm Epigenetic Modificationmentioning
confidence: 99%
“…For instance, epidemiologic evidences showed that environmental challenges imposed on the father, such as stress, specific diets, toxins, tobacco smoking and alcohol consumption, have been found to influence the development of the offspring via the non-genetic alterations within sperm including small non-coding RNAs, DNA damage, DNA methylation and histone modifications (Chen et al 2016b, Rando 2016, Schagdarsurengin & Steger 2016, Fullston et al 2017.…”
Section: Obesity Influences Sperm Epigenetic Modificationmentioning
confidence: 99%
“…These reproductive toxicities observed in C. elegans included reduced brood size, fertilized egg, and spermatide activation [6]. There is growing evidence that certain environmental effects can be passed to offspring via paternally pathways without changes in the sperm genome [7, 8]. Paternal information exists not only in the genome, but also in related specific epigenetic markers, mRNA content, and non-coding RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Such information could eventually be used to tailor personalised medicine approaches, based on relative genetic and epigenetic contributions to disease predisposition. For example, we know that diet directly impacts on sperm quality and influences the reproductive health of offspring [61]. This kind of ‘sperm epi-genotype’ data could not only inform public health messages targeted at males planning parenthood, but also help identify the potential causes (and thus therapeutic options) of medical conditions which occur in later generations.…”
Section: Using Sperm Epigenetics To Inform Preventative and Therapeutmentioning
confidence: 99%